Does EFSA statement on Monacolin content of nutraceutical combinations impair their lipid lowering effect? The LopiGLIK experience - Alessia Izzo; Rosa Costanzo; Lucia De Martino; Salvatore Di Napoli (Clinical Diabetes and Endocrinology)
Abstract Background Monacolin-K, the active component of red yeast rice (RYR), reduces cholesterol by inhibiting HMG-CoA reductase. Following safety concerns, the European Food Safety Authority (EFSA) recommended limiting Monacolin-K intake to less than 3 mg/day due to adverse effects at higher doses. Case presentation : A study comparing Armolipid Plus® and LopiGLIK® found LopiGLIK® more effective in lowering LDL cholesterol, possibly due to slightly higher dosages of Berberine and Monacolin-K. Despite reducing Monacolin-K content to 2.99 mg following EFSA guidelines, LopiGLIK® maintained its cholesterol-lowering efficacy. Conclusions Taken together, our results indicate that other ingredients, such as Morus alba, may contribute to LopiGLIK®’s enhanced effectiveness, challenging the notion that minor differences in Monacolin-K dosage account for the observed efficacy.